Hydrothermal-assisted synthesis and photoluminescence of ZnO microrods - N. Ekthammathat (2018)
© 2015 Inst Materials Physics. All rights reserved. Zinc oxide microrods were grown on Zn foils by a simple hydrothermal method. The XRD and SEM experimental results revealed the dense microrod-like wurtzite ZnO structure grown on Zn foils. The photoluminescence (PL) spectra at room temperature were measured. ZnO microrods exhibit photoluminescence broad emission at 500–650 nm using an excitation wavelength of 215 nm. By Gaussian analysis, it shows a maximum intensity at about 540 nm and a shoulder peak at around 570 nm which correspond to interstitial oxygen [O i – ] and oxygen vacancies [V O + ], respectively.